Crime and punishment analysis: land invasion "Para-institutions" in Cali (2014)
Based on the crime economics of Becker (1968) and Ehrlich (1973), including the impact of the migratory flow, this paper studies the reasons why some individuals choose to strategically, rationally, and contingently become involved in illegal land invasion "para-institutions" in Cali since the 1950s -- This will be done by modeling the efficiency of justice in order to discourage invaders through simulations of sentences and arrest likelihood and deterrent punishment under three "para-institutions": invasive dynasty, organized invasion and contingent invasion (endogenous migratory flow.) -- These simulations will be anchored to calibrated actual parameters of the relevant population -- This will allow the calibration of the line of indifference (division) among individuals with invasive (and incentives to illegality) and non-invasive behaviors -- Finally, a policy proposal will be devised to help correct the inefficiencies found in the sanctioning mechanisms, if applicable